The Anti-Oxidative, Anti-Inflammatory, Anti-Apoptotic, and Anti-Necroptotic Role of Zinc in COVID-19 and Sepsis - George Briassoulis; Panagiotis Briassoulis; Stavroula Ilia; Marianna Miliaraki; Efrossini Briassouli (MDPI AG, 2023)
Zinc is a structural component of proteins, functions as a catalytic co-factor in DNA synthesis and transcription of hundreds of enzymes, and has a regulatory role in protein-DNA interactions of zinc-finger proteins. For many years, zinc has been acknowledged for its anti-oxidative and anti-inflammatory functions. Furthermore, zinc is a potent inhibitor of caspases-3, -7, and -8, modulating the caspase-controlled apoptosis and necroptosis. In recent years, the immunomodulatory role of zinc in sepsis and COVID-19 has been investigated. Both sepsis and COVID-19 are related to various regulated cell death (RCD) pathways, including apoptosis and necroptosis. Lack of zinc may have a negative effect on many immune functions, such as oxidative burst, cytokine production, chemotaxis, degranulation, phagocytosis, and RCD. While plasma zinc concentrations decline swiftly during both sepsis and COVID-19, this reduction is primarily attributed to a redistribution process associated with the inflammatory response. In this response, hepatic metallothionein production increases in reaction to cytokine release, which is linked to inflammation, and this protein effectively captures and stores zinc in the liver. Multiple regulatory mechanisms come into play, influencing the uptake of zinc, the binding of zinc to blood albumin and red blood cells, as well as the buffering and modulation of cytosolic zinc levels. Decreased zinc levels are associated with increasing severity of organ dysfunction, prolonged hospital stay and increased mortality in septic and COVID-19 patients. Results of recent studies focusing on these topics are summarized and discussed in this narrative review. Existing evidence currently does not support pharmacological zinc supplementation in patients with sepsis or COVID-19. Complementation and repletion should follow current guidelines for micronutrients in critically ill patients. Further research investigating the pharmacological mechanism of zinc in programmed cell death caused by invasive infections and its therapeutic potential in sepsis and COVID-19 could be worthwhile.